2011
DOI: 10.1007/s10389-011-0443-1
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and physical activity among immigrants: a systematic review

Abstract: Aim The acculturation process presents numerous challenges that could benefit or adversely affect immigrants' health practices. The goal of this review was to present a systematic summary of studies examining the relationship between acculturation and physical activity among immigrants and ethnic minority populations. Subjects and methods Systematic review based on 44 original studies found in electronic databases (Psychinfo/ Psyndex, Eric, Pubmed/Medline, Web of Science, SportDiscus). Studies were eligible if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 76 publications
0
56
0
1
Order By: Relevance
“…This finding is inconsistent with Gerber’s systematic review which found physical activity to be positively associated with acculturation. 25 Greater health literacy was positively associated with physical activity levels in this population. This finding is consistent with a previous study showing a positive relation between physical activity and health literacy in older adults.…”
Section: Discussionmentioning
confidence: 74%
“…This finding is inconsistent with Gerber’s systematic review which found physical activity to be positively associated with acculturation. 25 Greater health literacy was positively associated with physical activity levels in this population. This finding is consistent with a previous study showing a positive relation between physical activity and health literacy in older adults.…”
Section: Discussionmentioning
confidence: 74%
“…Evidence of physical activity is inconsistent in terms of whether international students become more or less active after arriving in the US. In a review study, Gerber et al (2012) reported that among 44 studies that examined the relationship between acculturation and physical activity, 57% reported that acculturation was associated with higher leisure time physical activity, depending on gender, age, and ethnic background (Gerber et al, 2012). In another study, Yan and Cardinal (2013) found that Chinese international female students became more physically active after they arrived in the US.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a systematic examination of 44 articles associated with acculturation and physical activity, Gerber, Barker, and Puhse (2012) found that more than 50% of all studies showed that acculturation is positively associated with physical activity involvement. Kandula and Lauderdale (2005) examined the relationship between physical activity and acculturation among Asian Americans.…”
Section: Literature Reviewmentioning
confidence: 99%